Pengembangan dan Validasi Media Edukasi Pengaturan Makan bagi Penderita Hipertensi: Development and Validation of Leaflet Educational Media Food Management for People with Hypertension - Adinda Nova Mawwarda; Meirina Dwi Larasati; Ria Ambarwati (UNIVERSITAS NGUDI WALUYO, 2024)
Hypertension increases the risk of cardiovascular disease and stroke. An unhealthy diet and lack of knowledge about proper eating arrangements are major factors in the high rise in cases of hypertension. Therefore, it is necessary to develop more specific education to help regulate the eating of hypertensive patients. Develop and analyze the validity of the material, media leaflet on DASH diet meal regulation as an educational medium for hypertension in the work area of the Pecangaan Health Center. This study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The research subjects consisted of 2 material validators, 2 media validators, and 10 respondents with hypertension. Data collection involves the validity of material experts and media experts, as well as the response of people with hypertension through filling out questionnaires. The results were analyzed descriptively quantitatively and qualitatively using CVI. Material experts and media experts gave very feasible results on all aspects with a score> 0.80. The trial on 10 respondents received a good assessment. The average score of respondents on the material aspect (78%) is feasible category while the appearance and presentation aspect (82.5%) is very feasible category. Implementation of leaflet educational media for people with hypertension received a score of 81% with a very feasible category without suggestions, criticism, or input. The development of leaflet media is very feasible as a medium for educating hypertensive patients related to dietary management. ABSTRAK Hipertensi meningkatkan risiko penyakit kardiovaskular dan stroke. Pola makan yang tidak sehat dan kurangnya pengetahuan tentang pengaturan makan yang tepat menjadi faktor utama dalam tingginya kenaikan kasus hipertensi. Oleh karena itu, diperlukan pengembangan edukasi yang lebih spesifik untuk membantu pengaturan makan pasien hipertensi. Mengembangkan dan menganalisis validitas materi, media leaflet tentang pengaturan makan diet DASH sebagai media edukasi bagi hipertensi. Penelitian ini menggunakan metode Research and Development (R&D) dengan pendekatan ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subyek penelitian terdiri dari 2 validator materi, 2 validator media, dan 10 responden dengan hipertensi. Pengumpulan data melibatkan validitas ahli materi dan ahli media, serta respon penderita hipertensi melalui pengisian angket. Hasil analisis secara deskriptif kuantitatif dan kualitatif menggunakan CVI. Ahli materi dan ahli media memberikan hasil sangat layak pada semua aspek dengan skor >0,80. Uji coba pada 10 responden mendapatkan penilaian yang baik. Skor rata-rata responden pada aspek materi (78%) kategori layak sedangkana aspek tampilan dan penyajian (82,5%) kategori sangat layak. Implementasi media edukasi leaflet pada penderita hipertensi mendapatkan skor 81% dengan kategori sangat layak tanpa saran, kritik, atau masukan. Pengembangan media leaflet sangat layak sebagai media edukasi pasien hipertensi terkait pengelolaan diet.